PENGARUH EKSTRAK KULIT BUAH MANGGIS (Garcinia mangostana L.) TERHADAP PENAMPILAN REPRODUKSI MENCIT (Mus musculus L. Swiss Webster) - Hutapea, Renidawati; Sumarmin, Ramadhan; Widiana, Rina (STKIP PGRI Sumbar, 2014)
ABSTRACT Mangosteen is one of the traditional medicinal herb which is expected to be antifertilitas. In these plants contain chemical Xanthon. The components Xanthon this contains. Mangostin which is the active substance, from this plant that acts an antifertilitas. Mangostin serves to prevent cell division (Sitokinesis). This study aims to determine the effect of mangosten pell extract (Garcinia Mangostana L.). On reproductive performance of mice (Mus Musculus L.Swiss webster). This research is the use of animal experiments female mice (Mus Musculus L. Swiss Webster) as much as four treatment and six repeat. Treatment given is mangosteen rind extract with various dose namely: Treatment is A the control, without being given the mangosteen. Rind extract, treatment B,C, and D treatment is given mangosteen extract twenty-four days. With each dose B,C, and D parameter was observed holding weight. Parameters measured were the parent weight, the amount of the corpus luteum, Implantation, reseption, fetal death, fetal life and the average body weight of the fetus. Data were tasted by ANOVA (Analisis of varians) are parametric, then a further test with BNT on the degre 5%. The results showed that extracts of mangosteen rind (Garcinia Mangostana L.) effect on weight gain that is the parent of each treatment were significantly different when compered with control. The average number of corpus luteum and implanation has decreased in B,C, and D when compared with controls A. Fetus life experience decreased in dose B,C,and D when compared to the control A. It can be concluded that mangosteen peel extract fed orally for twenty-four dayas. Parent cause weight gain, a decrease in the amount of the corpus luteum, a decrease in the number of Implantation and decrease the number of live feuteus.